Efficiency of flow-through system for seed production of Tor putitora (Hamilton) at Bhimtal, Kumaon Himalaya - Sehgal, K L; Malik, D S (Indian Journal of Fisheries, 2011)
The golden or Himalayan mahseer (Tor putitora),oneof the most thrilling sports fishes in the world, has been classified recently as one of the threatened species of the Himalayan region and hence needs rehabilitation. This involves intensive aquaculture of this species to produce its seed for planting the streams and lakes. The first attempt which met with success was made by Tripathi (1977). Attempts of Sehgal and Kumar (1977) and Pathani and Das (1979) met with partial success. Joshi (1981) and Joshi and Sexena (1989) undertook preliminary work on seed production of T. putitora at Bhimtal by adopting techniques of Tripathi (1977).